Returning citizens: Social inclusion and occupational justice for mental health service users - Hamer, Helen (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2017)
This paper argues that social inclusion for service users can be enhanced through occupational justice and the protection of their rights as citizens to have meaningful employment. The paper will present a brief overview of citizenship and the importance of being included as a full participant in the democratic functioning of the state. The paper will then define social inclusion and what this means for people with mental health problems. The context of the current politics in the workplace and within mental health services and how this can impact on the vocational and occupational support of service users is also addressed. Empirical findings in both New Zealand and Brazil on social inclusion will be presented followed by international recommendations for future practice and policy that supports social inclusion. Initiatives in the sphere of employment for service users in both countries is also summarised. The paper will conclude by presenting the opportunities to increase the number of service user in the workforce and the impact this has on their sense of inclusion and connection on their return to the city, and their home, as citizens